Application of Hydroponic Technology to Enhance the Economic Independence of Rural Communities - Rahmania, Nurani; Sureni, Sureni; Hendratama, Handik; Tatsar, Mohammad Zaky; Zuhri, Zainullah (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service project focuses on addressing the issue of limited agricultural land and the need for efficient farming solutions in Bangsri Village. The main objective is to improve the economic independence of the community through the implementation of hydroponic technology, enabling them to cultivate crops in limited spaces. The approach used is Asset-Based Community Development (ABCD), which empowers the local community by utilizing existing resources. The project involves training, providing necessary equipment, and offering ongoing assistance in maintaining and harvesting the crops. The results indicate a significant increase in crop yields and economic benefits for participating households. Additionally, the community has gained new skills in hydroponic farming, enhancing both food security and income. This initiative has shown promising outcomes in enhancing agricultural productivity and economic sustainability in the village